Understanding the Large‐Scale Influence of Levees on Floodplain Connectivity Using a Hydrogeomorphic Approach. (11th January 2019) - Scheel, Kara; Morrison, Ryan R.; Annis, Antonio; Nardi, Fernando
Abstract: The widespread construction of levees has reduced river–floodplain connectivity and altered associated fluvial processes in many river systems. Despite the recognition that levees can alter floodplain connectivity, few studies have examined the role of levees in reducing floodplain areas at large watershed scales. This paper explores the application of a hydrogeomorphic floodplain inundation model in the Wabash Basin, located in the Midwestern United States, to assess changes in floodplain area in levee‐protected areas. We evaluate 10‐ and 30‐m topographic resolutions and spatially examine the influence of levees on floodplain area in relation to river network attributes. Generally, floodplains in levee‐protected areas were influenced by topographic resolution, stream order, and elevation details of levees found in topography datasets. We show, when compared to Federal Emergency Management Agency maps, our approach underpredicts floodplain area when using 10‐m resolution topography data but only slightly overpredicts when using 30‐m resolution data. After removing details of levees from topography data, we found changes in floodplain area varied spatially, but basin‐aggregate results changed little compared to topography datasets that contain levees, though larger floodplain areas were produced in some regions where levees were removed. This work contributes to a growing research emphasis on using hydrogeomorphic floodplain models to understand floodplain disconnectivity. Abstract : Research Impact Statement : A simple model for determining floodplain boundaries was used to estimate the loss of floodplain area caused by levees in a large basin.